2012
DOI: 10.3233/jad-2012-112105
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter mRNA Levels in Alzheimer's Disease Postmortem Brain

Abstract: Zinc (Zn2+) is concentrated into pre-synaptic vesicles and co-released with neurotransmitter at some synapses. Zn2+ can accelerate assembly of the amyloid-β peptides (Aβ) and tau protein central to the neuropathological changes found in Alzheimer's disease (AD). Altered protein levels of the membrane Zn2+ transporters ZnT1, ZnT4, and ZnT6 have been reported in AD postmortem brain tissue. The present study analyzed mRNA levels of five established (LIV1, ZIP1, ZnT1, ZnT4, and ZnT6) and one potential (PRNP) Zn2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…Recent studies showed alterations in levels of ZnTs proteins in the brain of subjects diagnosed with the preclinical stage of AD (PCAD), mild cognitive impairment (MCI), early (EAD), and the late (LAD) stage of AD when compared to the control subjects (Lovell et al, 2005, 2006; Smith et al, 2006; Lovell, 2009; Lyubartseva et al, 2010; Lyubartseva and Lovell, 2012). Human postmortem brain tissue from Braak-staged individuals with AD displayed a reduced expression of ZnT-3 mRNA (Beyer et al, 2009) and increased mRNA levels of the other more established zinc transporters, such as LIV1, ZIP1, ZnT1, ZnT6 in the AD cortex (Beyer et al, 2012). Also animal studies have linked dyshomeostasis in the brain zinc level to the pathogenesis and progression of AD.…”
Section: Zinc and Alzheimer's Diseasementioning
confidence: 99%
“…Recent studies showed alterations in levels of ZnTs proteins in the brain of subjects diagnosed with the preclinical stage of AD (PCAD), mild cognitive impairment (MCI), early (EAD), and the late (LAD) stage of AD when compared to the control subjects (Lovell et al, 2005, 2006; Smith et al, 2006; Lovell, 2009; Lyubartseva et al, 2010; Lyubartseva and Lovell, 2012). Human postmortem brain tissue from Braak-staged individuals with AD displayed a reduced expression of ZnT-3 mRNA (Beyer et al, 2009) and increased mRNA levels of the other more established zinc transporters, such as LIV1, ZIP1, ZnT1, ZnT6 in the AD cortex (Beyer et al, 2012). Also animal studies have linked dyshomeostasis in the brain zinc level to the pathogenesis and progression of AD.…”
Section: Zinc and Alzheimer's Diseasementioning
confidence: 99%
“…As zinc bound to Ab oligomers can disrupt synaptic function and contribute to neuronal cell death, decreased ZnT3 expression may result from the selective loss of zinc-secreting synapses. While Znt1 expression is increased in the temporal lobe of patients with early-or late-onset AD, low levels are associated with PCAD and mild cognitive impairment (MCI) (Lovell et al 2005;Lyubartseva et al 2010;Beyer et al 2012). A recent study found that mRNA levels of several zinc transporters (ZIP 1 and 6 as well as ZnT 1, 4, and 6) increase with AD progression correlating with NFT accumulation (Beyer et al 2012).…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…While Znt1 expression is increased in the temporal lobe of patients with early-or late-onset AD, low levels are associated with PCAD and mild cognitive impairment (MCI) (Lovell et al 2005;Lyubartseva et al 2010;Beyer et al 2012). A recent study found that mRNA levels of several zinc transporters (ZIP 1 and 6 as well as ZnT 1, 4, and 6) increase with AD progression correlating with NFT accumulation (Beyer et al 2012). Therefore, further analysis of zinc distribution in PCAD and MCI is required to further our understanding of how zinc metabolism changes through AD progression.…”
Section: Risk Of Zinc Deficiency In the Elderlymentioning
confidence: 99%
“…This potentially reflects the size and complexity of the zinc proteome, predicted to encompass approximately 2800 catalytic and regulatory proteins with an array of varied cellular functions 61 . Altered expression of Zip and ZnT proteins has been reported for various neurodegenerative disorders, including AD 62, 63 and Friedrich’s Ataxia 64 . We have also detected loss of Zip7 in 3 natural CLN6 disease models (Fig.…”
Section: Discussionmentioning
confidence: 99%